Exploring PBI New Student Anxiety in Learning Process - Chairun Riesa Al-Vitha Meugoe Meugoe (Journal of Islamic Mental Health and Development, 2026)
The transition into novel academic environments frequently precipitates significant anxiety among incoming students. While a normative psychological response to unfamiliar circumstances, such affective states can substantially impede cognitive engagement and learning efficacy. This study specifically investigates the manifestations of anxiety experienced by new students within the English Language Education (PBI) program during their initial learning processes. Its primary objectives are twofold: to delineate the specific dimensions of academic anxiety encountered and to analyze the coping mechanisms students employ to mitigate its effects. A qualitative methodological framework was adopted for this inquiry. Data were collected through semi-structured interviews, which were supplemented by an analysis of supporting documentation to triangulate findings and elucidate salient themes emerging from the interview narratives. The analysis reveals that student anxiety is not monolithic but manifests across three distinct, interrelated domains: 1) anxiety stemming from achievement motivation and gender-based performance expectations, 2) anxiety related to the fear of making linguistic errors and perceived deficiencies in vocabulary, and 3) anxiety induced by interactions with instructors perceived as strict or demanding. Despite the prevalence and intensity of these anxieties, findings indicate that students progressively develop and deploy adaptive strategies, demonstrating a capacity for psychological adjustment and resilience within the academic context.